Gestão de dados em arquiteturas de microsserviços - Ferreira, Luís Miguel Sousa (2021)
Currently, the information explosion significantly driven by the widespread use of services has become a challenge. The systems can now be redistributed or subdivided into small services, called microservices. However, this process makes the system extra complex, because although on the one hand, it simplifies the installation and management of the software, on the other hand, it increases the management difficulty due to the high number of interactions. In a scalable and large-scale system, it is difficult to assess which components have the greatest influence on the waiting time measured by users, so effective data management is fundamental. However, these components cannot be analyzed separately and the use of source code makes it difficult to correlate and identify the source of bugs or incorrect data. Therefore, it is essential to have a well-designed solution that matches the needs of the system. The study of an internationally renowned company was carried out to achieve the best solution to data management. An analysis of bibliographic references was also carried out, thus producing a complete approach to the theme. Through qualitative research and company analysis, this work aims to address the concepts of data management areas in microservices architectures, listing their characteristics, culminating with the presentation of a set of recommendations and solutions for some challenges encountered in this management and with the development of a data consistency monitoring tool. This case study focused on microservice architectures whose complexity of their systems and the volume of data are very high, reaching hundreds of thousands of transactions per second.